Formation mechanism of the Nb2C phase in the Nb–1Zr–0.1C (wt.%) alloy and interrelation between γ, β and α-Nb2C carbide phases. (15th April 2016) - Vishwanadh, B.; Krishna, K.V. Mani; Upadhyay, A.; Banerjee, R.; Arya, A.; Tewari, R.; Fraser, H.L.; Dey, G.K.
Abstract: In the present investigation, the formation of γ-Nb2 C in the Nb–Zr–C alloy and its interrelation with other Nb2 C carbide phases (α, β) has been studied. The use of synchrotron X-ray diffraction experiments, crystallographic analysis, high resolution imaging, as well as the determination of the relevant orientation relationship, between the second phase and matrix, has led to a proposed mechanism of γ-Nb2 C. It has been shown that the transformation of Nb to γ-Nb2 C takes place by the occupation of octahedral sites in the bcc Nb lattice by carbon atoms. The mechanism proposes minimal movement of Nb atoms during formation of γ-Nb2 C. Further, it has been shown that the sequence of phase transformations (γ-Nb2 C → β-Nb2 C → α-Nb2 C) involves ordering of vacancies whereas the basic lattice in all these three structures remains essentially same. First principle calculations aimed at calculating the formation energies of these carbides have revealed that the difference in these energies to be rather low. This rationalized the observation of a metastable disordered structural phase (γ-Nb2 C) in the present study. It has been shown that the arrangement of the carbon atoms in the γ-Nb2 C phase leads to the accumulation of strain along the [0001] direction which is accommodated by the creation of lattice defects. This strain destabilizes the γ-Nb2 C phase and leading to its dissolution at temperatures as low as 800 °C. Graphical abstract: